Fear of Missing Out (FOMO) as a Psychological Strategy in Digital Marketing - Gunawan Gunawan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2024)
This study aims to analyze the use of Fear of Missing Out (FOMO) as a psychological strategy in digital marketing and its impact on consumer behavior. FOMO is a psychological phenomenon characterized by an individual's fear of missing out on valuable experiences or information that others are having, and it has become increasingly relevant in the digital era filled with instant information and social media. FOMO strategies in digital marketing are often implemented through techniques such as limited-time offers, countdown timers, user testimonials, and product exclusivity. This research employs a descriptive-qualitative method with a literature study approach and content analysis of digital campaigns from various brands. The findings indicate that the application of Fear of Missing Out (FOMO) strategies in digital marketing effectively increases consumer interest and purchase speed. Consumers are more likely to make immediate purchases when offered promotions with time limits, limited stock, or exclusive services for first buyers. Additionally, positive testimonials and recommendations from previous buyers further strengthen trust and influence purchase decisions. Thus, FOMO strategies have been proven to significantly increase conversion rates and strengthen the relationship between consumers and brands.